Good Corporate Governance, Coorporate Social Responsibility, Leverage dan Nilai Perusahaan Manufaktur - Muria Siddhi, Putri Ari Prabandari; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 34 No 5 (2024), 2024)
This study aims to examine the effect of good corporate governance on disclosure of corporate social responsibility and leverage on firm value. The elements of good corporate governance are proxied to be the board of commissioners, independent commissioners, board of directors, and audit committee in manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange in 2016-2019. The sample was selected using the purposive sampling technique, analyzed by multiple linear regression. Results show good corporate governance as proxied by board of commissioners, independent commissioners, and audit committee affects firm value. However, the board of directors does not affect company value. Corporate social responsibility and leverage affects firm value. Keywords: Good Corporate Governance; Corporate Social Responsibility; Leverage; Nilai Perusahaan